IMPLEMENTASI KEBIJAKAN PENDIDIKAN DASAR DAERAH KEPULAUAN ( Suatu studi di Kecamatan Manganitu Selatan Kabupaten Kepulauan Sangihe Provinsi Sulawesi Utara) - GIGHILE, PRISKILA NATALIA; TULUSAN, FEMMY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
Basic education in the area of the Sangihe Islands Regency, especially in Manganitu Selatan sub-district, has constraints in fulfilling educator resources in accordance with skills and expertise in the field, the deficiency resulted in the program not running in accordance with the expected procedures and objectives. Implementation of this study aims to find out how the implementation or implementation of policies in education, especially primary school education in Southern Manganitu District, using descriptive qualitative research methods. The results of this study indicate that, the fulfillment of educators or resources in South Manganitu District is not in accordance with what is expected, proved in the study that the number of existing resources is not balanced with the number of primary school classes, the result of these shortcomings can affect the learning system for students because every educator should be concurrent in teaching and not in accordance with the abilities and areas they travel. Likewise in the existing financial management, as evidenced by the lack of facilities or facilities in school infrastructure is still lacking. Based on these conclusions, the researcher suggests that the resources of educators in Manganitu Selatan sub-district should be improved for the fulfillment of the quality and life of the next generation of the nation starting from the elementary school level, all forms of operational management must be implemented in accordance with established procedures for implementation a policy that has been planned for the realization of a common goal. Keywords: Policy Implementation, Basic Education, Archipelago Region.